2023
DOI: 10.1021/acs.iecr.3c01262
|View full text |Cite
|
Sign up to set email alerts
|

Study on Effect and Mechanism of Alkaline Earth Metal Poisoning on Cu/SSZ-13 Catalysts for Selective Catalytic Reduction of NOx with NH3

Abstract: In order to study the poisoning effect of the alkaline earth metal on Cu/SSZ-13 and reveal the poisoning mechanism, Cu/SSZ-13 zeolite catalysts were synthesized by the ion-exchange method and poisoned by different concentrations of Mg and Ca. The results of SCR tests and characterizations showed that the SCR activity of Cu/SSZ-13 catalysts decreased obviously after Mg or Ca poisoning, which is because Mg and Ca reduced the Cu 2+ species and Brønsted acid sites in Cu/SSZ-13, while increasing the content of Cu x… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…The SEM images present irregular-shaped and rod-shaped morphologies of the raw spent denitration catalyst. The EDS spectra analyses of regions (a) and (b) indicated that the major irregular particles contained W and Ti, whereas rod-shaped particles as binders mainly contained other elements, such as Al, Si, and V. Moreover, the V was encapsulated in the mineral phase with the V-bearing lattice structure (Al–Si–O–V compound) attributed to the prolonged high-temperature sintering during the denitration catalytic process. Obviously, only if the V-bearing lattice structure was destroyed by the leaching solvent could ensure a high leaching rate of V …”
Section: Resultsmentioning
confidence: 99%
“…The SEM images present irregular-shaped and rod-shaped morphologies of the raw spent denitration catalyst. The EDS spectra analyses of regions (a) and (b) indicated that the major irregular particles contained W and Ti, whereas rod-shaped particles as binders mainly contained other elements, such as Al, Si, and V. Moreover, the V was encapsulated in the mineral phase with the V-bearing lattice structure (Al–Si–O–V compound) attributed to the prolonged high-temperature sintering during the denitration catalytic process. Obviously, only if the V-bearing lattice structure was destroyed by the leaching solvent could ensure a high leaching rate of V …”
Section: Resultsmentioning
confidence: 99%
“…Nitrogen oxides (denoted NO x ) emitted from stationary and mobile sources are one of the major air pollutants, which lead to diverse environmental problems such as photochemical smog, haze, and acid rain. , Due to its low cost, simple equipment, and high catalytic denitration efficiency, selective catalytic reduction of NO x with NH 3 (denoted NH 3 -SCR) has become a mainstream process for reducing NO x emission in the flue gas. , V 2 O 5 –WO 3 /TiO 2 (denoted VWTi), which consists of 1–2 wt % V 2 O 5 as an active component and 3–8 wt % WO 3 as a promoter supported on TiO 2 , is the most extensively used catalyst system in the SCR process . This is primarily attributed to its stable high denitrification efficiency and suitable operating temperature range for coal-fired plants.…”
Section: Introductionmentioning
confidence: 99%